Evaluation of three sampling methods for the microbiological analysis of broiler carcasses after immersion chilling - Giombelli, Audecir; Cavani, Ricardo [UNESP]; Gloria, Maria Beatriz Abreu (Elsevier, 2013)
Countries have different official programs and implement different sampling methods for the detection of Salmonella on poultry carcasses. In Brazil, a 25-g sample of skin and muscle excision (SME) from the wings, neck, and pericloacal parts is used; in the European Union (EU), a 25-g sample of neck skin (NSE) is used; and, in the United States, the whole carcass is rinsed with 400 ml of diluent (WCR). In the present study, these methods were evaluated to compare Salmonella occurrence and counts of hygiene indicator microorganisms (Escherichia coli, Enterobacteriaceae, and total viable count of aerobic mesophilic bacteria) using different carcasses from the same flock and also using different analytical units taken from the same carcass. Eighty flocks, with four broiler carcasses from each, were included in this study; three broilers were sampled according to protocols from Brazil, the EU, and the United States, and the last one by all three methods. SME, NSE, and WCR provided equivalent results (P > 0.05) for Salmonella detection on broiler carcasses when using different carcasses from the same flock and when using the same carcass. The predominant serovar was Salmonella Enteritidis. For the enumeration of hygiene indicator microorganisms, WRC provided higher counts than SME or NSE (P < 0.05), when using both the same or different carcasses. Therefore, it is possible to directly compare Salmonella results in poultry carcasses when using the methods recommended by the legislative bodies of Brazil, the United States, and the EU. However, WCR provides the best results for hygiene indicator microorganisms. Copyright © International Association for Food Protection.